Respostas
respondido por:
1
-x²+7x-6=0
/\ = 7² - 4*(-1).(-6)
/\ = 49 -24
/\ = 25
x = -7 + - √25/ -2
x' = -7 + 5 / -2 = 1
x'' = -7 - 5 / -2 = -6
S= {1; -6)
/\ = 7² - 4*(-1).(-6)
/\ = 49 -24
/\ = 25
x = -7 + - √25/ -2
x' = -7 + 5 / -2 = 1
x'' = -7 - 5 / -2 = -6
S= {1; -6)
respondido por:
1
7x - x² - 6 = 0
x² - 7x + 6 = 0
a = 1
b = -7
c = 6
Delta:
Δ = b² - 4ac
Δ = (-7)² - 4 * 1 * 6
Δ = 49 - 24
Δ = 25
Bhaskara:
x = - b ± √Δ / 2a
x = - (-7) ± √25 / 2 * 1
x = 7 ± 5 / 2
x' = 7 - 5 / 2 = 2 / 2 = 1
x'' = 7 + 5 / 2 = 12 / 2 = 6
Espero ter ajudado. Valeu!
x² - 7x + 6 = 0
a = 1
b = -7
c = 6
Delta:
Δ = b² - 4ac
Δ = (-7)² - 4 * 1 * 6
Δ = 49 - 24
Δ = 25
Bhaskara:
x = - b ± √Δ / 2a
x = - (-7) ± √25 / 2 * 1
x = 7 ± 5 / 2
x' = 7 - 5 / 2 = 2 / 2 = 1
x'' = 7 + 5 / 2 = 12 / 2 = 6
Espero ter ajudado. Valeu!
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás